Taxonomy of the ceratophysellan lineage (Collembola: Hypogastruridae) in the light of laboratory hybridization studies - Skarúyºski, Dariusz (Zootaxa, 2005)
The results of recent laboratory hybridization studies on the ceratophysellan lineage species are synthesized, and their impact on the taxonomy of this lineage is discussed. The discovered rule that morphological similarity is proportional to the reproductive isolation degree and in consequence to the relationship between species is a good basis for distinguishing species with potential for classification of the ceratophysellan lineage. The morphological and biological species concepts appear to be fully compatible, and Schaefferia emucronata, S. willemi, Ceratophysella denticulata, C. engadinensis, C. stercoraria, C. silvatica, and C. granulata appear to be species consistent with the general lineage concept. The proposed new classification of the ceratophysellan lineage (composed of two genera: C. denticulata group + Typhlogastrura + Schaefferia and C. armata group + Bonetogastrura) is tested against the results of laboratory hybridization studies. The probable monophyly of Schaefferia and polyphyly of Bonetogastrura and Typhlogastrura show that the phylogeny of the ceratophysellan lineage is more complicated than suggested by presently accepted and proposed classifications. The obtained results are only a premise, and the probability of the conclusion being correct would increase with the number of such tests.